Heart rate responses during gradually increasing and decreasing exercise in water - Nishimura, K.; Nose, Y.; Yoshioka, A.; Kawano, H.; Onodera, S.; Takamoto, N. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of this study was to determine the heart rate (HR) responses during and after gradually increasing and decreasing exercise in water and on land. Eight healthy Japanese males volunteered for this study. Subjects performed arm cranking exercise (calibration and triangular tests) for 32 -min and recovered for 1 -min. HR and cardiac autonomic nervous system activity were continuously measured. The amplitude and phase lags at the top and bottom of the work rate were measured in each cycle. The results were as follows; 1) the HR phase response was shorter in water than on land, but there were no differences in amplitude, 2) reactivation in cardiac parasympathetic nerve was greater in water. Thus, exercise and recovery in water may enhance the stability of autonomic nervous activity, not only during exercise but also after exercise.